Current management of choledocholithiasis after bariatric surgery - Alzahrani, Khalid M.; Jafri, Sumayyah A.; Hamdi, Hafiz A. (International Surgery Journal, 2021)
The increasing prevalence of obesity all over world has led to a growing number of metabolic and bariatric surgeries. Bariatric surgery is more effective for weight loss than medical therapy, with Roux-en-Y gastric bypass (RYGB) being considered the gold standard of care over the past decade. Bariatric surgery and the subsequent weight loss are associated with an increased risk for the development of gallstone formation. Common bile duct stones prevalence around 10% among patients with symptomatic gallbladder stones. Choledocholithiasis can be technically challenging problem to treat in patients post-laparoscopic RYGB (LRYGB) or a biliopancreatic diversion (BPD/DS) due to the altered upper gastrointestinal anatomy. This review describes the different treatment options of common bile duct stones after malabsorptive bariatric surgery, success rate, and adverse effects of each treatment modality including enteroscopy-assisted endoscopic retrograde cholangiopancreatography (EA-ERCP), percutaneous transhepatic cholangiography (PTC), endoscopic ultrasound-directed transgastric retrograde cholangiopancreatography (EDGE), and laparoscopic-assisted ERCP (LAERCP).